IMPLEMENTATION OF FUTURES LITERACY LABS AS A REALIZATION OF THE 17TH POINT OF SDG IN DISASTER RISK REDUCTION - Oesman, Duta Aksara S. (Universitas Nasional, 2024)
This research is motivated by the urgency to find new way of looking at Disaster Risk Reduction (DRR) in the TUNA (Turbulent, Uncertain, Novel, Ambiguous) era after the COVID-19 pandemic. The purpose of this research is to explain the implementation of UNESCO's Futures Literacy Labs international system or strategy in realising the 17th SDG point on disaster risk reduction. This research uses a qualitative approach with descriptive methods to understand the meaning of the research objectives. The theory used in this research is constructivism theory. The results of this study found that Futures Literacy Labs are able to create a space of togetherness and cooperation to respond and form a collective understanding of the future, by utilising imagination, communication, and overcoming the boundaries that may exist in views and actions related to disaster risk.